2014
DOI: 10.1111/ped.12443
|View full text |Cite
|
Sign up to set email alerts
|

Anxiety sensitivity: Changes with puberty and cardiovascular variables

Abstract: AS, which is reported to be a trait-like variable, may change during adolescence, due to the effect of pubertal growth and blood pressure interacting with AS during adolescence.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 71 publications
(108 reference statements)
0
6
0
Order By: Relevance
“…A few studies have connected AS to indicators of cardiovascular disease (e.g., Norman & Lang, ; Seldenrijk et al., ), but to our knowledge, there are few studies on the association between AS and blood pressure. In a study of healthy adolescents (Akça, Ağaç Vural, Türkoğlu, & Kılıç, ), AS was associated with higher diastolic blood pressure even when controlling for age, sex, and pubertal stage. Two other studies found that, compared to healthy controls, individuals with hypertension report higher levels of AS (Delle Chiaie et al., ; Pagotto, Fallo, Fava, Boscaro, & Sonino, ).…”
Section: Pathophysiological/pathomechanical Alterationsmentioning
confidence: 98%
“…A few studies have connected AS to indicators of cardiovascular disease (e.g., Norman & Lang, ; Seldenrijk et al., ), but to our knowledge, there are few studies on the association between AS and blood pressure. In a study of healthy adolescents (Akça, Ağaç Vural, Türkoğlu, & Kılıç, ), AS was associated with higher diastolic blood pressure even when controlling for age, sex, and pubertal stage. Two other studies found that, compared to healthy controls, individuals with hypertension report higher levels of AS (Delle Chiaie et al., ; Pagotto, Fallo, Fava, Boscaro, & Sonino, ).…”
Section: Pathophysiological/pathomechanical Alterationsmentioning
confidence: 98%
“…Those with high levels of anxiety sensitivity may be particularly vulnerable to panic attacks. Adolescents self-reported higher anxiety sensitivity in the early stages of puberty than in the later stages, but did not report sex differences (45). In a study of healthy adolescents ages 12–17 years, those with more advanced pubertal status and increased emotional reactivity were most likely to experience panic symptoms in a hyperventilation challenge, after controlling for age and gender (46).…”
Section: Epidemiology Of Anxiety Disorders Across the Female Lifespanmentioning
confidence: 99%
“…Adolescents are at a critical point in the transition from child to adults, involving a variety of physiological, psychological, and social function upheavals (e.g., genital development and pubic hair growth) that are stressful events for them [ 14 , 15 ]. A robust body of research indicates that pubertal status is a key predictor of various internalizing and externalizing problems for adolescents that influence the resilience of adolescents [ 16 , 17 ].…”
Section: Introductionmentioning
confidence: 99%